2009
DOI: 10.1002/chem.200901781
|View full text |Cite
|
Sign up to set email alerts
|

A Coordination Controlled Aryl–Halide Oxidative Addition to Platinum

Abstract: Aryl À halide bond activation and coordination of unsaturated substrates are key steps in many metal-mediated carbonÀcarbon bond-forming reactions. [1, 2] Numerous experimental and computational studies have been reported on these processes.[3] The electronic nature of the reactants is known to affect both steps. In particular, an electron withdrawing group (EWG: e.g., CF 3 , CN, NO 2 ) makes the C aryl À halogen bond more ionic, weakens this bond, and therefore increases the rate of the bond activation (Sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…The substituent effect on the C–N bond cleavage was not cleanly correlated with the Hammett substituent constants, but the electron-donating substituent, such as OMe and Me groups, increased the reactivity of the C–N bonds. Therefore, the subsitutent effect observed here on the C–N bond cleavage is opposite to that of Wolczanski’s tantalum-mediated C–N bond cleavage and the general tendency of oxidative addition of polar aromatic C–X bonds. , …”
Section: Resultscontrasting
confidence: 85%
“…The substituent effect on the C–N bond cleavage was not cleanly correlated with the Hammett substituent constants, but the electron-donating substituent, such as OMe and Me groups, increased the reactivity of the C–N bonds. Therefore, the subsitutent effect observed here on the C–N bond cleavage is opposite to that of Wolczanski’s tantalum-mediated C–N bond cleavage and the general tendency of oxidative addition of polar aromatic C–X bonds. , …”
Section: Resultscontrasting
confidence: 85%
“…On the other hand, van der Boom and co-workers demonstrated that the reaction of Pt(0) or Ni(0) with a bromostilbene derivative resulted in selective η 2 -CC coordination, which was kinetically preferred at low temperature, followed by intramolecular “ring walking” of the metal center and intramolecular oxidative addition of the aryl-bromide bond, which was thermodynamically preferred when the temperature was raised . In accordance with this result, density functional theory calculation suggested that η 2 -CC coordination is more stable than the free state…”
mentioning
confidence: 75%
“…Representative examples are the 1,3-metal-shift processes encountered by allyl, propargyl, and allenyl complexes [2] and, more generally, the shifts of metal centers over p-conjugated systems (including metal walking along rings and chains, haptotropic shifts, and so forth). [3][4][5] Strikingly, most studies have focused thus far on monometallic complexes, and, comparatively, metal-shift processes have only been rarely evidenced and studied in polymetallic complexes. [6] On the one hand, the unique properties associated with the presence of several metal centers make their dynamic behavior all the more interesting to be studied.…”
Section: Introductionmentioning
confidence: 99%